1983
DOI: 10.1128/jb.155.1.97-106.1983
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of maltose transport in Escherichia coli: conditions affecting import of maltose-binding protein into the periplasm of calcium-treated cells

Abstract: The reconstitution of active transport by the Ca2+-induced import of exogenous binding protein was studied in detail in whole cells of a malE deletion mutant lacking the periplasmic maltose-binding protein. A linear increase in reconstitution efficiency was observed by increasing the Ca2+concentration in the reconstitution mixture up to 400 mM. A sharp pH optimum around pH 7.5 was measured for reconstitution. Reconstitution efficiency was highest at 0°C and decreased sharply with increasing temperature. The ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…The present experiments extend the application of the reconstitution procedure with calcium-permeabilized cells (5,6) in one significant way. Until now, proteins introduced into the periplasm by this technique have always been rather acidic, and hence negatively charged at the pH (7.0) used for reconstitution (6). MBP from E. aerogenes and S. marcescens, however, is basic ( Fig.…”
Section: Discussionmentioning
confidence: 55%
“…The present experiments extend the application of the reconstitution procedure with calcium-permeabilized cells (5,6) in one significant way. Until now, proteins introduced into the periplasm by this technique have always been rather acidic, and hence negatively charged at the pH (7.0) used for reconstitution (6). MBP from E. aerogenes and S. marcescens, however, is basic ( Fig.…”
Section: Discussionmentioning
confidence: 55%
“…2). Strains LA5440 (mglBSSO) and LA6221 (mglBSOI), which carry missense mutations in mglB (7,8), were complemented to mgl+ by plasmid pHG15 by using the criterion of restoration of wild-type transport activity (data not shown). This result indicated that GBP from S. typhimurium could replace E. coli GBP and functionally interacts with membrane components of the E. coli mgl transport system.…”
Section: Resultsmentioning
confidence: 99%
“…30 mM). This concentration of MBP gives good transport rates when maltose transport is reconstituted (11). The suspension was shaken at 0°C for 30 min, and the cells were then gently washed with 1 ml of 0.9% NaCl at room temperature.…”
Section: Growth Of Cells Overnight Cultures In Minimal Medium Himentioning
confidence: 99%
“…We have recently developed a technique whereby soluble substrate-binding proteins can be introduced into the periplasmic space after Ca2+induced permeabilization of the outer membrane of gramnegative bacteria. Import and function of these proteins can be demonstrated by the reconstitution of transport in mutants lacking binding protein (10,11).…”
mentioning
confidence: 99%